Protective Role of Indole-3-Acetic Acid Against Salmonella Typhimurium: Inflammation Moderation and Intestinal Microbiota Restoration - Yuxin Fan; Qinglong Song; Siyu Li; Jiayu Tu; Fengjuan Yang; Xiangfang Zeng; Haitao Yu; Shiyan Qiao; Gang Wang (Microorganisms)
Indole-3-acetic acid (IAA), a metabolite derived from microbial tryptophan metabolism, plays a crucial role in regulating intestinal homeostasis. However, the influence and potential applications of IAA in the context of animal pathogen infections remain underexplored. This study investigates the prophylactic effects of IAA pretreatment against Salmonella typhimurium (ST) SL1344 infection, focusing on its ability to attenuate inflammatory responses, enhance intestinal barrier integrity, inhibit bacterial colonization, and restore colonic microbiota dysbiosis. The results demonstrated that IAA ameliorated the clinical symptoms in mice, as evidenced by reduced weight loss and histopathological damage. Furthermore, IAA inhibited the inflammatory response by downregulating the gene expression of pro-inflammatory cytokines IL-17A, TNF-α, IL-1β, and IL-6 in colon, ileum, and liver. IAA also preserved the integrity of the intestinal mucosal barrier and promoted the expression of tight junction proteins. Additionally, 16S rRNA gene sequencing revealed significant alterations in intestinal microbiota structure induced by ST infection following IAA treatment. Notable changes in β diversity and species richness were characterized by the enrichment of beneficial bacteria including Bacteroideaceae, Spirillaceae, and Bacillus. The proliferation of Salmonella enterica subspecies enterica serovar Typhi was significantly inhibited, thereby enhancing the intestinal health of the host. In summary, the oral administration of IAA contributes to the alleviation of inflammation, restoration of the intestinal barrier, and correction of colonic microbiota disturbance in mice challenged with ST.